Development of Interactive Teaching Materials in Reflective Microteaching for Prospective Teacher Students - Muliaman, Agus; Wahdi Ginting, Fajrul; Rezkia Lukman, Isna; Mellyzar, Mellyzar; Juliani Harahap, Emi; Sri Rejeki, Nimas (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
Reflective-based interactive media in microteaching is a valuable tool for improving teaching and developing teacher professionalism. Through the use of digital technology and a structured process of reflection, teachers can more effectively identify weaknesses in their teaching practices and make necessary improvements. This research aims to develop interactive teaching materials in reflective microteaching learning to shape the professional character of prospective teachers. This research is development research using the ADDIE model which has 5 development stages, namely analysis, design, development, implementation, dan evaluation, Due to time constraints, this research is still limited to this stage development due to research limitations. The validation results from material and media experts stated that this teaching material was very valid with a percentage score of 95.09% and 96.25% respectively in the